Climate change, adaptation, and global jobs: Lessons and urgent policy options for Africa - Agba, A. M. Ogaboh; Akpanudoedehe, John J.; Ojong, Felix E.; Agba, Michael Sunday (Quantitative Economics and Management Studies, 2021)
Climate change remains one of the world’s greatest challenge in the 21st century. It causes inevitable changes that alter human activities. Adaptation to climate change creates and at the same time limits opportunities that support human existence. While United States of America, Europe, China, India and other countries are maximizing the opportunities climate change adaptation offers especially in areas of green technology, energy and agriculture, that of Africa who are more vulnerable to climate change are complacent and at most show less commitment. As the negative impacts of climate change increases and livelihoods erode, and as jobs continue to disappear leading to conflicts and upheavals in Africa, governments across the continent need policy options that will enable them to mitigate and adapt to climate change while at the same time address the problem of unemployment and create new patterns of livelihood. This paper, therefore, explores options that support these objectives. It offered policy suggestions in green energy and agriculture where Africa have a comparative advantage over other nations, and which also has the capacity of employing 90 per cent of the continent's workforce. It makes suggestions on how Lake Chad and other water sources affected by climate change in Africa can be revived to support agricultural activities and hydropower industry as well as create green jobs. It advocated for investment in biofuel, wind and solar energies to create green jobs. The paper submits that if green jobs are created and agricultural activities supported conflicts associated with unemployment and migration will be reduced drastically.